2010
DOI: 10.7326/0003-4819-152-3-201002020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Treatment of the Complex Regional Pain Syndrome

Abstract: Association of Anaesthetists of Great Britain and Ireland, University College London Hospitals Charity, and CSL-Behring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 32 publications
2
106
1
8
Order By: Relevance
“…Among 6 patients with long-standing CRPS, some benefited from therapeutic plasma exchange [69]. One open-label study in 11 patients with CRPS and 1 well-designed, RCT in 12 patients reported modest efficacy of IVIg, 1 g/kg [70,71]. Given the desperate situation of patients with refractory CRPS, some of whom resort to limb amputation to try and reduce their pain, larger trials of IVIg and other immunomodulatory therapies seem indicated.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Among 6 patients with long-standing CRPS, some benefited from therapeutic plasma exchange [69]. One open-label study in 11 patients with CRPS and 1 well-designed, RCT in 12 patients reported modest efficacy of IVIg, 1 g/kg [70,71]. Given the desperate situation of patients with refractory CRPS, some of whom resort to limb amputation to try and reduce their pain, larger trials of IVIg and other immunomodulatory therapies seem indicated.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Case study data suggests anti-TNF therapy may have a role in CRPS (Ozgül et al 2011) but controlled trial data is still awaited. Goebel et al (2010) have demonstrated a significant reduction in pain for 5 out of 12 people with CRPS treated with low-dose intravenous immunoglobulin in a randomised controlled trial. This pain relief lasted for five weeks on average.…”
Section: Pharmacologicalmentioning
confidence: 98%
“…These changes in cytokine activity are not associated with disease duration or other clinical signs but appear to be related specifically to the degree of mechanical hyperalagesia, rather than pain per se, as they remain high even when the pain disappears (Wesseldijk et al 2008). Autoantibodies in some patients with CRPS have been reported by a number of groups (Blaes et al 2004;Goebel et al 2010;Kohr et al 2011) but it is not yet clear whether the autoantibodies are pathogenic or potentially protective against future reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…IVIG with steroids has been successful in one third of patients with CRPS. 18 Both thalidomide and lenalidomide have also shown some benefit in the treatment of CRPS. 19,20 Converging evidence supports the development of a sterile inflammatory response at the site of injury in CRPS patients.…”
Section: Case Reportmentioning
confidence: 99%